Can Empathy, Other Personality Attributes, and Level of Positive Social Influence in Medical School Identify Potential Leaders in Medicine?. (April 2015) - Hojat, Mohammadreza; Michalec, Barret; Veloski, J. Jon; Tykocinski, Mark L.
Abstract : Purpose: To test the hypotheses that medical students recognized by peers as the most positive social influencers would score (1) high on measures of engaging personality attributes that are conducive to relationship building (empathy, sociability, activity, self-esteem), and (2) low on disengaging personality attributes that are detrimental to interpersonal relationships (loneliness, neuroticism, aggression-hostility, impulsive sensation seeking). Method: The study included 666 Jefferson Medical College students who graduated in 2011–2013. Students used a peer nomination instrument to identify classmates who had a positive influence on their professional and personal development. At matriculation, these students had completed a survey that included the Jefferson Scale of Empathy and Zuckerman–Kuhlman Personality Questionnaire short form and abridged versions of the Rosenberg Self-Esteem Scale and UCLA Loneliness Scale. In multivariate analyses of variance, the method of contrasted groups was used to compare the personality attributes of students nominated most frequently by their peers as positive influencers (top influencers [top 25% in their class distribution], n = 176) with those of students nominated least frequently (bottom influencers [bottom 25%], n = 171). Results: The top influencers scored significantly higher on empathy, sociability, and activity and significantly lower on loneliness compared with the bottom influencers. However, the effect size estimates of the differences were moderate at best. Conclusions: The research hypotheses were partially confirmed. Positive social influencers appear to possess personality attributes conducive to relationship building, which is an important feature of effective leadership. The findings have implications for identifying and training potential leaders in medicine.